Giberela do trigo: viabilidade técnica da integração de estratégias de manejo visando racionalização do uso de fungicidas e redução de micotoxinas - Oliveira, Duane Nascimento (2023)
Fusarium head blight is the most difficult disease to control in wheat, causing damage to grain quality, mainly due to the production of mycotoxins. The current management of the disease is done with the use of fungicides, combined with cultivars with levels of resistance to the pathogen. Thus, the objectives of this study were to evaluate the behavior of the Fusarium head blight and the resulting production of mycotoxins under the management strategies adopted in wheat crops. That way, two cultivars with different levels of resistance to the disease were used, a highly susceptible and moderately resistant cultivar, combined with application or not of fungicide at different phenological stages. The crops were installed in an irrigation pivot area and a rainfed area, being cultivated for two years. For the application (0, 1, 2 or 3) of fungicides (tebuconazole and trifloxystrobin) the pre-anthesis phase; anthesis (moment of anther extrusion) and seven days after anthesis. Thus, through the evaluations carried out following a phenological scale, the FH index (GI - Incidence x severity), damage to the grains (D - % weight loss), weight per unit volume, hectoliter weight (kg/hct ⁻¹), yield calculation (t/ ha⁻¹), concentration (ug/kg⁻¹) and chemotypes of mycotoxins found in the wheat samples were determined. Through the results obtained, the treatments that did not receive fungicide applications showed averages of up to 115.5% higher in (IG) and (D), when compared to the plots that received application. The parameter (kg/hct⁻¹) showed no significant difference between treatments, and the quantitative parameter, tons per hectare (t/ha⁻¹) had averages between 32% and 48.5% higher in treatments with two and three fungicide applications. Applications seven days after anthesis were less efficient when compared to other applications. Mycotoxin concentrations were 14.7% higher in moderately resistant material. The mycotoxin chemotypes found in the samples were: deoxynivalenol (DON), 15-acetyl-deoxynivalenol (15-ADON), 3-acetyl DON (3-ADON) and DON-3-Glc (D3G). In the present study, through the evaluations carried out, a significant difference was found between the fungicide applications in the proposed phenological stages. The treatments were efficient in controlling the disease, not demonstrating the same performance on the production and accumulation of mycotoxins in wheat cultivars.